Contrast-Enhanced Endoscopic Ultrasonography for Pancreatic Tumors. (18th May 2015) - Yamashita, Yasunobu; Kato, Jun; Ueda, Kazuki; Nakamura, Yasushi; Kawaji, Yuki; Abe, Hiroko; Nuta, Junya; Tamura, Takashi; Itonaga, Masahiro; Yoshida, Takeichi; Maeda, Hiroki; Maekita, Takao; et al.
Abstract : Objectives . To investigate the usefulness of contrast-enhanced endoscopic ultrasonography (CE-EUS) for histological differentiation of pancreatic tumors. Methods . CE-EUS was performed for consecutive patients having a pancreatic solid lesion, and tumors were classified into three vascular patterns (hypervascular, isovascular, and hypovascular) at two time phases (early-phase and late-phase). Correlation between vascular patterns and histopathology of resected pancreatic cancer (PC) tissues was ascertained. Results . The final diagnoses of 147 examined tumors were PC ( n = 109 ), inflammatory mass ( n = 11 ), autoimmune pancreatitis ( n = 9 ), neuroendocrine tumor ( n = 8 ), and others ( n = 10 ) . In late-phase images, 104 of 109 PCs had the hypovascular pattern, for a diagnostic sensitivity and specificity of 94% and 71%, respectively. Of 28 resected PCs, 10 had isovascular, and 18 hypovascular, patterns on the early-phase image. Early-phase isovascular PCs were more likely to be differentiated than were early-phase hypovascular PCs (6 well and 4 moderately differentiated versus 3 well, 14 moderately, and 1 poorly differentiated, P = 0.028 ) . Immunostaining revealed that hypovascular areas of early-phase images reflected heterogeneous tumor cells with fibrous tissue, necrosis, and few vessels. Conclusion . CE-EUS could be useful for distinguishing PC from other solid pancreatic lesions and for histological differentiation of PCs.